A Study of Histopathological Changes of Suprarenal Glands in Cases of Ante-mortem Burn Deaths - Ahmed, Raihan Uddin; Mahanta , H K (Journal of Indian Academy of Forensic Medicine, 2015)
In case of agonal death like burn, hanging or other form of asphyxial death various histopathological changes occur in the suprarenal glands. Sometimes under certain circumstances the diagnosis of death by ante-mortem burn becomes difficult. The histopathological changes in suprarenal glands will probably help in these cases to arrive at a diagnosis of ante-mortem burn deaths. This study comprised of suprarenal glands dissected out during medico-legal autopsies from 35 cases of deaths due to burn brought to the mortuary of Department of Forensic Medicine, Assam Medical College & Hospital, Dibrugarh from 1st June 2012 to 31st May 2013. This study revealed that definite histopathological changes occur in the suprarenal glands in a considerable number of cases of death due to burn (57.14%). Bilateral adrenal hemorrhage is rarely diagnosed clinically as its presentation is generally non-specific. The clinical importance of bilateral adrenal hemorrhage is that it may lead to acute adrenal insufficiency and possible death. Therefore, when a sudden deterioration in a patient with thermal injuries is encountered, adrenal insufficiency must be considered. The findings of the present study show the relation between stress and its effects on the suprarenal glands.